KEWENANGAN MENTERI HUKUM DAN HAK ASASI MANUSIA DALAM PENYELESAIAN SENGKETA PERATURAN PERUNDANG-UNDANGAN MELALUI JALUR NONLITIGASI - Rasyid Tanjung; Masril Masril (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2022)
Abstract: This study examines the authority of the Ministry of Law and Human Rights in carrying out legal dispute resolution through non-litigation channels based on the Minister of Law and Human Rights Regulation Number 2 of 2019. The method used in this study is normative legal research. In analyzing using prescriptive analysis method with inductive logic. The results of this study indicate that regarding the Authority of the Ministry of Law and Human Rights in Settlement of Legislative Disputes Through the Non-litigation Path that the author has carried out, the Ministry of Law and Human Rights is not authorized to settle disputes over laws and regulations, because the settlement of disputes over laws and regulations The law is the authority of the judiciary (Supreme Court), while the Ministry of Law and Human Rights is the executive body. Keywords: Authority, Ministry of Law and Human Rights, Legal Dispute Resolution, Non Litigation.